Pengembangan Modul Digital Menggunakan Flip PDF Professional Pada Pembelajaran Tematik Terpadu di Kelas V Sekolah Dasar - Khairiyah, Arifatul; Muhammadi, Muhammadi (Universitas Negeri Padang, 2024)
This research is motivated by the lack of variety of learning resources used in schools and not fully utilizing technology in its development. The aim of the research is to develop valid and practical digital-based modules using the Flip PDF Professional application to support the successful implementation of